Moringa oleifera and Musa sapientum ameliorated 7,12-Dimethylbenz[a]anthracene-induced upregulations of Ki67 and multidrug resistance 1 genes in rats - Akinlolu, Adelaja; Oyewopo, Adeoye; Kadir, Risikat; Lawal, AbdulMalik; Ademiloye, Jesutolani; Jubril, Abdullahi; Ameen, Mubarak; Ebito, Gabriel (International Journal of Health Sciences, 2021)
Objectives: Moringa oleifera (MO) and Musa sapientum (MS) are plants of ethnomedicinal importance. We evaluated the effects of MOF6 (extracted from MO leaves) and MSF1 (extracted from MS suckers) on immunomodulations of Ki67 (proliferation biomarker) and multidrug resistance 1 (MDR1) genes in the liver of rats in 7,12-Dimethylbenz[a]anthracene (DMBA)-induced hepatotoxicity and mutagenesis to determine their antiproliferation, anti-drug resistance, and anticancer potentials. Methods: Forty-five adult male rats were randomly divided into nine groups (n = 5). Groups 1 and 2 received physiological saline and 15 mg/kg bodyweight of DMBA, respectively. Groups 3 and 4 received 15 mg/kg bodyweight DMBA and were treated with 15 and 30 mg/kg bodyweight of MOF6, respectively. Group 5 received 15 mg/kg bodyweight DMBA and was treated with 10 mg/kg bodyweight of MSF1. Group 6 received 15 mg/kg bodyweight DMBA and was treated with 3.35 mg/kg bodyweight of doxorubicin and intravenous injection of 0.5 ml/200 g of cisplatin. Groups 7–9 received only 15 and 30 mg/kg bodyweight of MOF6 and 10 mg/kg bodyweight of MSF1, respectively. DMBA, doxorubicin, and extracts doses were administered orally. The duration of our experimental procedure was 8 weeks. Consequently, liver histopathology (hematoxylin and eosin technique) and enzyme-linked immunosorbent assay homogenates’ concentrations of Ki67 and MDR1 were evaluated. Computed data were statistically analyzed (P ≤ 0.05). Results: Results showed normal histoarchitectures of the liver in all groups. Statistical analyses showed significant (P ≤ 0.05) and non-significant decreased concentrations (P ≥ 0.05) of Ki67 and MDR1 in Groups 3–9 compared with Group 2. Therefore, MOF6 and MSF1 ameliorated DMBA-induced hepatotoxicity, abnormal proliferation, and drug resistance. Conclusion: MOF6 and MSF1 possess antiproliferation, anti-drug resistance, and anticancer potentials.